The Situation of Korean Small and Medium-Sized Business Investment in Lao PDR and the Lao Government's Promotion Strategy - DUANGPASITH, Phatsa; SOMSAMONE, Vilayphone; SIFONGXAY, Sangthong; OUNPHOUVONG, Stamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objectives of this study were to: 1.) provide an overview of small and medium-sized business investment in the Republic of Korea; Korea in the Lao People's Democratic Republic 2.) Guidelines for delivering investment to Lao PDR's Korean small and medium business owners. The research team conducted qualitative research this time. Employees from the Ministry of Industry and Trade, the National Statistics Department, the Small and Medium Enterprise Promotion Department, and the Ministry of Planning and Investment comprise the sample group. There are ten people in all. The interview questionnaire was used in the research study to analyze the data by arranging the importance of the studied issues, finding differences, interpreting and analyzing the content, considering the appropriateness and completeness of the data, and summarizing the results in accordance with the set objectives. Research results revealed that South Korea has been a major investor in Laos in recent years. Korean companies have invested in a wide range of sectors, and their investment has helped boost the Lao economy. The Lao government is committed to attracting more foreign investment, and Korean companies are likely to continue to play a major role in the Lao economy in the years to come. Korean investment in Laos has been increasing steadily over the past 10 years, reaching $289.6 million in 2022. This is due to Laos's strategic location, growing economy, and political stability. Korea is interested in investing in Laos in a variety of sectors, including infrastructure, energy, and agriculture. Korean investment is playing a significant role in Laos's economic development, helping to create jobs, improve infrastructure, and boost trade. Korean entrepreneurs who have invested in Laos have found that the market is diverse and has the potential for growth. Guidelines for the Promotion of Small and Medium Enterprises: The state encourages and promotes the development of small and medium enterprises with the goal of creating the ability to compete in production, trade, and services through financial assistance, technical assistance, technology, marketing, scientific research, and so on. The state promotes regional and international cooperation in the work of promoting small and medium-sized enterprises, such as productivity work, by sharing lessons and information, upgrading personnel knowledge and skills, transferring technology, seeking aid, and others on the basis of independence, equality, and mutual benefit, and acting in accordance with Lao agreements and international conventions to which the PDR is a party.